Permainan Kartu Gambar Dengan Metode Cantol Roudhoh Di Kelompok B TK Mahkota Selong - Maulidian, Muslihatul; Suhirman, Suhirman; Ramdani, Zuhut (Universitas Hamzanwadi, 2019)
This research was based on the students tack to recognize the word in learning. This study aims to improve the ability of word recognition through drawing card games using the cantol roudhoh method in group B TK Mahkota Selong in the 2017/2018 academic year. This type of research was Classroom Action Research which is a teacher who plays a direct role in the learning process. The subjects of this study were students of group B TK Mahkota Selong in the academic Year 2017/2018 consisting 25 student. While the object of this research was the application of cantol roudhoh method in improving the ability of word recognition through flashcard games in group B TK Mahkota Selong. Based on the results of the study, the average percentage of the ability of word recognition in group B TK Mahkota Selong before treatment was 33% for the alternative answer